Helping the healer: population-informed workplace wellness recommendations for physician well-being. (27th March 2018) - Brooks, E; Early, S R; Gendel, M H; Miller, L; Gundersen, D C
Abstract: Background: The need to keep physicians healthy and in practice is critical as demand for doctors grows faster than the supply. Workplace wellness programmes can improve employee health and retain skilled workers. Aims: To broaden our understanding about ways to help doctors coping with mental health problems and to develop population-informed workplace wellness recommendations for physician populations. Methods: Researchers surveyed physicians to document potential warning signs and prevention strategies. A survey was issued to doctors who presented to a physician health programme with mental health complaints. The survey captured respondents' feedback about how to identify and prevent mental health problems. Data were analyzed using simple descriptive statistics. Results: There were 185 participants. Half of respondents believed their problems could have been recognized sooner and 60% said they exhibited signs that could aid in earlier detection. Potential warnings included fluctuations in mood (67%), increased comments about stress/burnout (49%) and behavioural changes (32%). To improve detection, prevention and care-seeking for mental health problems, doctors endorsed multiple items related to the use of interpersonal supports, personal factors and organizational dynamics throughout the survey. Conclusions: The findings confirmed earlier work demonstrating the value of social and organizational support in maintaining physician health. It further indicated that earlier identification and/or prevention of mental health problems is not only possible, but that medical organizations are uniquely situated to carry out this work.